1987
DOI: 10.1017/s0021859600081144
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rates following intra-uterine insemination with pellet or straw-frozen ram semen

Abstract: There has been considerable research on techniques for artificial insemination of sheep with frozen ram semen (Maxwell, 1984). Acceptable pregnancy rates were reported following ‘two-step’ dilution and freezing of semen in P.V.C. ‘ministraws’ (Colas, 1975; Colas & Guerin, 1981); however, other workers have obtained poor fertility following cervical insemination with semen frozen in straws (Maxwell, etal. 1980; Tervit elal. 1984).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The obtained better post-thawed motility and plasma membrane integrity of ram spermatozoa in straws than in pelleted form proved in our study were also reported in goats (Bezerra et al, 2012), boar (Dai et al, 2009). Also, Hunton et al (1987) indicated that semen frozen in straws was more motile than pelleted semen, but both applied cryopreservation methods (pellets and straws) caused a decrease in the percentage of sperm livability. Pickett and Berndtson (1974) reported that superior sperm viability, greater storage efficiency, and higher conception rates resulting from storage in plastic straws have led to rapid increases in the use of this packaging technique.…”
Section: Discussionsupporting
confidence: 83%
“…The obtained better post-thawed motility and plasma membrane integrity of ram spermatozoa in straws than in pelleted form proved in our study were also reported in goats (Bezerra et al, 2012), boar (Dai et al, 2009). Also, Hunton et al (1987) indicated that semen frozen in straws was more motile than pelleted semen, but both applied cryopreservation methods (pellets and straws) caused a decrease in the percentage of sperm livability. Pickett and Berndtson (1974) reported that superior sperm viability, greater storage efficiency, and higher conception rates resulting from storage in plastic straws have led to rapid increases in the use of this packaging technique.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, AI was performed in the ewes selected one by one from MAP-, FGA-, CIDR-and P sponge-treated groups in order during the period of 44 to 52 h after removal of the intravaginal devices. The range of the fixed-time AI with frozen semen in the ewes treated with MAP or FGA sponge with eCG treatment at the time of sponge removal is generally 48 to 60 h [3,4,[27][28][29][30]. Nevertheless, when an eCG injection was given one day before the removal of the intravaginal sponges as in the present study, estrus was induced earlier than when the injection was given at the time of sponge removal [19,20].…”
Section: Discussionmentioning
confidence: 55%
“…Although the lower post-thawing motility of strawfrozen spermatozoa would suggest a reduction in the number of viable spermatozoa in the inseminate, we previously found no difference in the fertility of semen frozen by the straw and pellet methods when the number of motile spermatozoa was reduced to 5 x 10" (Ritar et al 19906). Similar findings in sheep led Hunton et al (1987) to suggest that it may be of questionable value to adjust the number of spermatozoa inseminated on the basis of post-thawing motility. However, they possibly did not reach a threshold where the number of motile spermatozoa may be critical to maintain fertility.…”
Section: Resultsmentioning
confidence: 70%